Crescimento e feminilização de larvas de jundiás Rhamdia quelen submetidas a dietas com hormônios esteróides femininos - Medeiros, Tanise dos Santos (2009)
The techniques of sex reversal serve to highlight existing advantages on one of the sexes in different fish species, several species of commercial interest have been considered in this respect. Recent studies show that in silver catfish there is higher growth in female compared to male, but there is still no data regarding dose, active hormone, or stage of development and application of hormones for sex reversal. Therefore, the objective of this study was to determine dose and active principles of female steroid hormone levels for sex reversal in catfish larvae, as well as evaluating its growth under the effect of these treatments. The inclusion of 10, 20, 40 and 50 mg/kg feed of estradiol benzoate and the active principles of estradiol: valerate, ciprionate and 17b-estradiol level of 30 mg/kg was tested for 20 days. Histological analysis of gonads at 40 days showed up to 96% females at doses 20, 40 and 50 mg/kg feed. Larvae fed the highest hormone level (50 mg / kg feed) had lower weight values compared to other treatments. There was no significant difference in survival between the larval treatments. Testing the active ingredients of estradiol up to seven days, the average weight of larvae of the diet without hormone was higher than the other treatments. At 21 days of the experiment only larvae of the treatment with ciprionate of estradiol showed lower weight compared to the other treatments, which did not differ between themselves. At 40 days of experiment the weight gain in larvae fed 30mg/kg of ciprionate of estradiol was superior to the others. There were no significant differences between treatments on sex reversal of the larvae by adding 30mg/kg of valerate, ciprionato, 17ß-estradiol and without hormone.